Chronic Kidney Disease and Nonalcoholic Fatty Liver Disease—Is There a Link?. (6th March 2014) - Orlić, L.; Mikolasevic, I.; Bagic, Z.; Racki, S.; Stimac, D.; Milic, S.
Abstract : Research in recent years has led to the recognition of the importance of nonalcoholic fatty liver disease (NAFLD) and its relationship to the metabolic syndrome (MS). This has led to a growing interest in the potential prognostic value of NAFLD for adverse cardiovascular disease (CVD) outcome. On the other hand, searching for new risk factors for chronic kidney disease (CKD) development and progression is very important. Growing evidence suggests that the MS is an important factor in the pathogenesis of CKD. The best confirmation of this pathogenic link is hypertensive and diabetic nephropathy as the main causes of CKD. Furthermore, the possible link between NAFLD and CKD has also attracted research interest and recent data suggest an association between these two conditions. These findings have fuelled concerns that NAFLD may be a new and added risk factor for the development and progression of CKD. NAFLD and CKD share some important cardiometabolic risk factors and possible common pathophysiological mechanisms, and both are linked to an increased risk of incident CVD events. Therefore, common factors underlying the pathogenesis of NAFLD and CKD may be insulin resistance, oxidative stress, activation of rennin-angiotensin system, and inappropriate secretion of inflammatory cytokines by steatotic and inflamed liver.